ANALISIS KOMPETENSI PEDAGOGIK GURU TAHFIDZ DALAM MEMBERIKAN KOREKSI DAN REINFORCEMENT LISAN MELALUI METODE TALAQQI DI MADRASAH IBTIDAIYAH - Adi Haironi; Adi Sartono; Muhamad Ihsan Heriyanto; Fiter Hafizon; Ihsan Mahendy; M. Wally Yuddin; Lalu Muhammad Gilang Saputra (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the pedagogical competence of Tahfidz teachers in providing oral correction and reinforcement through the talaqqi method in Islamic elementary schools (Madrasah Ibtidaiyah). The research focuses on teachers’ ability to manage Qur’anic memorization sessions, apply appropriate correction strategies, and implement effective verbal motivation during talaqqi interactions. Using a qualitative descriptive approach, data were collected through observation and in-depth interviews with Tahfidz teachers experienced in elementary-level Qur’anic instruction. The findings indicate that the teachers possess sufficient pedagogical competence to conduct talaqqi-based learning effectively. Oral corrections are generally delivered immediately (immediate correction) to maintain memorization accuracy, while articulation and pronunciation improvements are provided progressively according to students’ individual abilities. Verbal reinforcements such as “Ahsantum,” “Barakallahu fiikum,” and “Maa syaa Allah” serve as essential motivational tools that foster enthusiasm, learning persistence, and self-confidence among students. Major challenges include large class sizes, diverse memorization abilities, and limited time for personalized correction.